Generalizations of optimal growth theory: Stochastic models, mathematics, and meta-synthesis - Stephen Spear; Warren Young (Bar-Ilan University, Department of Economics, 2015)
This paper deals with the evolution of the "classical" growth research program of Ramsey-Cass-Koopmans vintage via its stochastic "variants" and "generalizations" (Samuelson 1976, note 1). Thus, here we trace the origins and impact of the stochastic generalization that brought about a paradigm shift in modern economics, and still generates significant research in the form of “quantitative macroeconomics”, that is to say, “real business cycle theory” (RBC henceforth), and its metamorphosis into the dynamic, stochastic general equilibrium (DSGE) approaches of both new Classical and new Keynesian vintage. The evolution of endogenous growth approaches and “New” and “Unified” growth models will be dealt with in a separate paper.
Keywords: 330